Role of Organic Manure and Green Manuring in the Maintenance of Soil Fertility in India - Raychaudhury, S.P. (Journal of Soil and Water Conservation, 2022)
The three important functions, among others, commonly attributed to bulky organic manures are :(1) It acts as a store-house of plant nutrients,(2) it promotes the activity of soil micro-organisms, and(3) it improves the physico-chemical properties of the soil. Although experimental evidence shows that generally the use of well-balanced fertilisers has given good results comparable to those obtained by the application of bulky organic manures, it has also been established by experimental results that injudicious use of fertilisers alone may lead to deterioration of the crop producing power of the soil. It is to be noted that organic manures harbour micro-nutrients needed by plants while fertilisers, unless specially prepared will not contain these. On this account organic manures are often considered as 'full proof' in the sense that one cannot go wrong with them, while with fertilisers their application must be done with certain amount of technical knowledge.